Impact of Charitable Donation and Female on Board on firm Value - WANG, Bingqi (2022)
The impact of corporate Charitable donation on firm value has been controversial. Board members act as prominent participants in corporate decision-making. Based on Chinese listed companies from 2011-2020 as a research sample, the findings of this thesis suggest that corporate charitable giving behaviour enhances corporate value， female board members play a positive moderating role between the two elements.